A violência contra a mulher, o espaço digital e o processo de desculpabilização do agressor numa narrativa fílmica - Boeira, Adriana da Silva (2023)
In Brazilian and global society, there has been an increase in violence against women, or perhaps now, there has been a less veiled exposure due to reporting channels and support networks for victims. Considering the broad and complex debate surrounding the topic, this dissertation focuses on analyzing discourses about acts of violence against women stemming from social media, using a docudrama as the research corpus. Although media spaces play an important social role, their platforms have contributed to a wider range of violent actions against women, such as harassment, threats, stalking, and the public exposure of their intimate moments by partners and former partners, with the purpose of humiliating, defaming, and publicly harming the victim. Understanding that there are socially evaluated behaviors considered better or worse due to deeply rooted social norms in a predominantly patriarchal and sexist society that has historically denied female autonomy, this research employs the theoretical framework of French Discourse Analysis. It problematizes, through scene excerpts and statements from the series "Digital Victims" (2019), how the discourse of violence finds support in a practice of exculpating the aggressor. The research assumes that the meaning effects produced by the series generate contradictory readings in relation to its stated objective by its creators, which is to identify women as victims and prompt society to reflect on the issue.The study shows that beyond this purpose, the analyzed excerpts reveal the presence of a punitive socio-historical memory regarding female behavior, which acts as a limiting and restraining force on what a woman can or cannot do in relation to her body, her sexuality, and her choices, thereby indicating a tolerance towards the actions of male subjects. The result achieved by this study is a further challenge to the linear and explicit discourse presented in the docudrama's objectives, aiming to give voice to women, as it demonstrates that social constraints must still be dismantled in order to achieve a condition of equity among individuals. In reality, there are particular issues affecting all women worldwide simply because they are women (ADICHIE, 2015). The vulnerability of women has its roots in the prejudice ingrained in the blank slates of social structures that prioritize the masculine over the feminine. Thus, this study sought to contribute to the reflections aimed at understanding the issue of violence against women, promoting the understanding that crimes and culpability can also be comprehended through different perspectives.